Prenatal ultrasonographic diagnosis and management of combined duodenal and esophageal atresia with tracheoesophageal fistula. Presentation of a case and review of the literature - Urviola, Richard (2015)
Duodenal atresia, the most frequent type of small intestine congenital obstruction, is present in 1 of each 10 000 live newborns and tends be associated to other malformations like esophageal anomalies and trisomies, mainly chromosome 21. Ultrasonography prenatal diagnosis consists of abdominal "double cys" image associated with polyhydramnios. On the other hand the esophageal atresia and variants are difficult to diagnose. The prenatal detection of a congenital malformation that requires surgery permits planning the delivery in an obstetrical unit, with rapid resuscitation and immediate surgical intervention of the neonate. The mortality is due to associated malformations or prematurity, with good out come in the isolated forms. A case of prenatal ultrasonographic diagnosis, management and evolution of a double duodenal and esophageal atresia with distal tracheoesophageal fistula is presented.